Acalypha godseffiana Leaves Restore Hydrogen Peroxide-Triggered Reno-hepatic Tissue Dysfunction and Oxidative Stress in Albino Rats - Samson Eruke Okoro (Chemistry and Biochemistry: Research Progress Vol. 3, 2025)
Background: Oxidative stress is a cellular state characterized by the immoderate release of reactive oxygen species (ROS) or weakening of the antioxidant defense system. Hydrogen peroxide (H2O2) can give rise to hydroxyl radicals in cells. H2O2 is a highly toxic membrane-permeable metabolic poison that can cause severe bioenergetic dysfunction and cellular damage if allowed to accumulate. Continued exposure to H2O2 can lead to the collapse of redox homeostasis and organ failure. Acalypha godseffiana has been traditionally used for the treatment of various ailments and is reported to contain phytochemicals with promising antioxidant and ameliorative properties. Objective: This study evaluated the efficacy of the aqueous extract of A. godseffiana leaves against H2O2-triggered oxidative stress and organ damage in Wistar rats by measuring hepatotoxic biomarkers, nephrotoxicity and the status of the antioxidant defense system. Study Design: Twenty-five adult Wistar rats weighing 150-200g, randomized into five groups were used in this study. The rats were acclimatized in a temperature-controlled animal house (25 ± 2 °C) under 12 h of light and 12 h of darkness for 10 d before the experiment. The rats were then housed in standard iron cages in groups of five rats each and given ad libitum access to standard food and water. Fresh leaves of A. godseffiana leaves were air-dried, ground into fine powder and used in the preparation of an aqueous extract. Methodology: Oxidative stress and toxicity were triggered using 5ml of 6% H2O2. Treated rats received 100, 200 and 400 mg/kg b.w of A. godseffiana aqueous leaf extract for 28 days. The rats were fasted for 24 h before sampling and then mildly anesthetized with chloroform. Blood samples were collected for biochemical analysis. The serum was separated by centrifugation at 3,000 g for 5 min and kept at -20°C until use for biochemical assay. The liver and kidney were excised and the tissues were preserved in formalin for histological investigations. All methods used in the study followed standard protocol. Results: There was a significant (P<0.05) increase in plasma levels of L - aspartate aminotransferase (AST) in the H2O2-treated group as compared with the negative control which recorded 105.00 ± 3.00 and 107.50 ± 7.50 (µ/L) at day 14 and 28 respectively. Plasma AST levels in groups 3 and 4 were 106 ± 1.00 and 111.50 ±1.50 (µ/L) on day 14, and 111.00 ± 1.00 and 108.00 ± 14.00 (µ/L) on day 28 indicating significant improvement when compared with values for the positive control group. The effect of the leaf extract on liver enzyme activity was dose-dependent, with 400mg/kg dose being more effective. The H2O2-group showed significant (P<0.05) increases in plasma levels of K-, Na+, Urea, Cl- and HCO3- as compared with the negative control. A. godseffiana treated rats showed a significant (P<0.05) increase in serum levels of GSH, Catalase and SOD. Photomicrographs obtained showed histologically distorted liver and kidney tissues in the H2O2 group on days 14 and 28. Overall, the architecture of the liver was preserved by the administered aqueous leaf extract of A. godseffiana. Conclusion: Data obtained from this study suggest that A. godseffiana exhibits promising antioxidant and hepato-protective potency in a dose-dependent manner. This position is supported by previously reported pharmacologically active compounds in A. godseffiana and its positive effects on the hemopoietic system, integrity and function of the liver and kidney in rats. The findings suggest that the leaves of A. godseffiana have the potential to restore reno-hepatic tissue dysfunction and oxidative stress. These potentials should be explored further as it may serve as a future therapy in the management of reno-hepatic tissue dysfunction oxidative stress.